Intraosseous keratin cyst of the distal phalanx - Rohini Prasad; Arivind Bhamidi; Arun Kumar Rajeswaran; Ramamurthy Bhuvaneshwari (Indian Journal of Plastic Surgery)
Keratin or epidermoid cysts of the phalanges are rare lesions mimicking osteolytic lesions such as infection, malignancy and other tumours. Definitive diagnosis can be made by histopathology only and treatment is by simple excision and curettage. We present a case of intraosseous keratin cyst of the distal phalanx and review of literature.